On Some Relations Involving the Ramanujan's Tau Function - Dr. R. Sivaraman; Prof. J. López-Bonilla; S.Vidal Beltrán, (Indian Journal of Advanced Mathematics (IJAM), 2026)
It is known a recurrence relation for the Ramanujan’s tau-function involving the sum of divisors function.